The Lands in the Process of Integration and Resistance to the Capitalist System: Theoretical Study and Empirical Demonstration - Piguave Espinoza , Edwin Ulises (2021)
Our objective is to find a structural explanation for the permanent conflict between extractivist populations, states, and transnational corporations in the territories semi-integrated to capitalism. We find irreconcilable structural contradictions between populations and transnational states in terms of their ways of distributing and using natural resources, which make conflict inevitable. These contradictions are solved by the capitalist system destroying native cultures and appropriating their resources through violence and dispossession. Then, a methodology was built to measure the level of conflict-dispossession in each planetary region.